Efficacy and safety of hepatic arterial infusion chemotherapy combined with programmed cell death protein-1 antibody and lenvatinib for advanced hepatocellular carcinoma - Xu, Yongkang; Fu, Shumin; Mao, Ye; Huang, Shenglan; Li, Dan; Wu, Jianbing (Frontiers in Medicine, 2022)
Abstract Background: To assess the efficacy and safety in patients with advanced hepatocellular carcinoma (HCC) who are undergoing hepatic arterial infusion chemotherapy (HAIC) combined with PD-1 antibody and lenvatinib. Methods: We retrospectively evaluated 61 patients treated with HAIC combined with PD-1 antibody and lenvatinib at the Second Affiliated Hospital of Nanchang University between September 2020 and January 2022 for advanced HCC. We analyzed tumor response,progression free survival (PFS) and Treatment-related adverse events (TRAEs). Results: The objective response rate (ORR) was 36.1% (RECIST 1.1)/57.4% (mRECIST) and the disease control rate (DCR) was 82.0%. The overall median PFS was 6.0 months, 6.7 months for first-line treatment and 4.3 months for second-line treatment. The most common TRAEs were neutropenia (50.8%), abdominal pain (45.9%), and aspartate aminotransferase increase (39.3%). Conclusion: HAIC combined with PD-1 antibody and lenvatinib is effective in the treatment of advanced HCC, and the TRAEs are generally controllable. Key words: Hepatic arterial infusion chemotherapy; PD-1 antibody; Lenvatinib; Hepatocellular carcinoma.